PENGARUH KEDISIPLINAN LOYALITAS DAN KEPEMIMPINAN TERHADAP PRODUKTIVITAS KERJA PADA SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN KEPULAUAN SELAYAR - Agustini Agustini; Syamsul Alam; Andi Djlalante (AkMen JURNAL ILMIAH, 2020)
This study aims to analyze whether there is an influence between Discipline, Loyalty and Leadership on Work Productivity at the Secretariat of the Regional People's Representative Council, Selayar Islands.The method used is descriptive quantitative method, the data used are primary data and secondary data generated from distributing questionnaires, direct observation and literature study. The analytical tool used is statistical analysis, namely multiple linear regression analysis with proof of the hypothesis through the t test to prove the relationship between the independent variable and the dependent variable partially and the f test to prove the relationship between the independent variable and the dependent variable simultaneously. The study was conducted by taking a sample of 88 respondents, which is the total number of employees at the Secretariat of the Regional People's Representative Council of the Selayar Islands Regency. This study proves that there is a positive but insignificant influence between the Discipline and Loyalty variables on Work Productivity and there is a positive and significant influence between the Leadership variable on Work Productivity at the Regional Representative Council Secretariat of the Selayar Islands Regency. This study also proves that there is a positive and significant influence between the variables of Discipline, Loyalty and Leadership simultaneously (simultaneously) on Work Productivity at the Secretariat of the Regional People's Representative Council of the Selayar Islands Regency. This study also shows that the leadership variable is the most dominant variable affecting Work Productivity at the Regional Representative Council Secretariat of the Selayar Islands Regency